Processamento e qualidade de compotas de figo diet e convencional - Caetano, Priscilla Kárim [UNESP]; Vieites, Rogério Lopes [UNESP]; Daiuto, Érica Regina [UNESP]; De Moura, Silvia Cristina Sobottka Rolim (FapUNIFESP (SciELO), 2017)
The objective of this research was to evaluate the physicochemical quality characteristics of diet and conventional fig jams. The fig variety used in this experiment was the cv. purple variety and different formulations with sweeteners were evaluated. The tests were carried out with nine treatments and three repetitions, giving a total of 27 samples. The syrup formulations were: sucrose (TA); sorbitol (TS); erythritol (TE); sorbitol and erythritol (TSE); stevioside (TST); sodium cyclamate, sucralose and sodium saccharin (TCSuSa); sodium cyclamate and sodium saccharin (TSC); acesulfame-K and sucralose (TAcSu); stevioside, sodium saccharin and sodium cyclamate (TSSC). In accordance with the literature and legislation for this type of product the physical and chemical attributes evaluated were pH, soluble solids, titratable acidity, reducing sugars, total reducing sugars, protein, lipid, ash and moisture contents, and the results obtained complied with the values found in the literature and the legislation for this type of product. With respect to the quality parameters, all the treatments showed satisfactory results, with the pH values ranging from 3.98 to 4.47, the presence of vacuum from 11 to 13 inches Hg and soluble solids contents ranging from 9.43 to 3.90 for the treatments with sweeteners. According to its characteristics, the product developed fitted into the category of diet products.
Processing and quality control of diet and conventional fig jams
Keywords: Description; Ficus carica L.; Sweetener.